A Comprehensive Review of Stem-Cell Therapy. Issue 8 (August 2017) - Elbuluk, Ameer; Einhorn, Thomas A.; Iorio, Richard
Abstract : Regenerative orthopaedics has been used as a biological alternative to conventional therapy and surgical intervention for treating musculoskeletal conditions associated with limited therapeutic options. Orthopaedic investigators have shown promising early clinical results by developing cell-based approaches to regenerate injured cartilage, tendon, ligaments, and bone. Despite continued research, issues regarding harvesting, delivery of treatment, cost, indications, and optimal timing of intervention must be considered. Multidisciplinary networks of investigators are essential to achieve the full clinical and therapeutic potential of mesenchymal stem cells in orthopaedics. Although mesenchymal stem cells offer great promise for the treatment of degenerative diseases and orthopaedic conditions, there is still a dearth of properly conducted controlled clinical studies.